2014
DOI: 10.1007/s10648-014-9279-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Sources of Individual Differences in Critical-Analytic Thinking: a Capsule Overview

Abstract: Critical-analytic thinking is typically conceived as a meta-construct that arises at the junction of a problem state (i.e., a situation that requires analysis that challenges previous assumptions) and an individual (i.e., an entity with the capacity to exercise critical-analytic thinking). With regard to the latter, there is a substantial body of research focusing on developmental and educational prerequisites for critical-analytic thinking. A less studied aspect of critical-analytic thinking pertains to indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 193 publications
(213 reference statements)
0
9
0
1
Order By: Relevance
“…Specifically, the authors posit that the control-oriented mechanisms needed to handle more than one language may require the release of extra dopamine in brain areas involved in control. There is also evidence that control-oriented mechanisms are heritable (Bolger et al, 2014). Finally, the potential importance of dopamine in language learning has also been pointed out in a seminal review by Wong, Morgan-Short, Ettlinger, and Zheng (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the authors posit that the control-oriented mechanisms needed to handle more than one language may require the release of extra dopamine in brain areas involved in control. There is also evidence that control-oriented mechanisms are heritable (Bolger et al, 2014). Finally, the potential importance of dopamine in language learning has also been pointed out in a seminal review by Wong, Morgan-Short, Ettlinger, and Zheng (2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Heijltjes, Van Gog, and Paas (2014) found that learning CT skills is potentiated by the combination of explicit CT instruction and practice. On the other hand, disciplinary differences could be due to individual characteristics that impact when time comes to enroll in a particular course from a certain disciplinary area (Badcock et al, 2010), seeing that neurocognitive systems, in interaction with life experiences, are responsible for individual differences in CT (Bolger, Mackey, Wang, & Grigorenko, 2014). Also, it is necessary to account for the impact of educational background, as suggested by Evens, Verburgh, and Elen (2013), who found that Secondary Education impacts the choice of disciplinary area, which relates to students' CT performance.…”
Section: Discussionmentioning
confidence: 99%
“…Intelligence has been defined as several interrelated intellectual abilities, organized as independent systems consisting of general abilities ( g factor), and specific abilities, such as “crystallized” knowledge ( Bolger, Mackey, Wang, & Grigorenko, 2014 ). Intelligence is no longer viewed as strictly genetically determined, but as determined by genetic as well as by environmental factors ( Bolger et al, 2014 ; Subotnik et al, 2011 ; Tucker-Drop & Harden, 2012 ).…”
mentioning
confidence: 99%
“…Intelligence has been defined as several interrelated intellectual abilities, organized as independent systems consisting of general abilities ( g factor), and specific abilities, such as “crystallized” knowledge ( Bolger, Mackey, Wang, & Grigorenko, 2014 ). Intelligence is no longer viewed as strictly genetically determined, but as determined by genetic as well as by environmental factors ( Bolger et al, 2014 ; Subotnik et al, 2011 ; Tucker-Drop & Harden, 2012 ). That is, the interaction between genetic, brain, and evironmental factors creates the diversity of cognitive functions that are regarded as human intelligence: Genetic factors establish the basis for the neurocognitive systems and the interaction between genetic and environmental factors determines the individual variation in intelligence ( Bolger et al, 2014 ).…”
mentioning
confidence: 99%